Penggunaan Kalium Feri Sianida Untuk Pengolahan Serum Ikterik - Sujono, Sujono; Sistiyono, Sistiyono; Widada, Subrata Tri (Jurnal Analis Kesehatan, 2023)
A bad sample gives an invalid laboratory test result. There are several reasons that can cause a sample to be unfit for examination. The serum that most often causes errors are hemolysis, jaundice and lipemia. Icteric serum is serum that is yellow brown due to hyperbilirubinemia (increased levels of bilirubin in the blood). Icteric serum may cause interference with laboratory tests. Icteric serum can affect measurements at a wavelength of 400-500 nm. Examination by the method of oxidase or peroxidase reactions, such as glucose, cholesterol, triglycerides and uric acid can be disrupted. Potassium Ferricyanide is added to oxidize bilirubin to biliverdin before testing, and can reduce absorption disorders. Potassium ferric cyanide can reduce total bilirubin levels (p=0.000) in icteric serum. There were differences in the results of total cholesterol (p=0.000), triglycerides (p=0.019), glucose (p=0.001), total protein (p=0.011), albumin (p=0.004), globulin (p=0.002), creatinine ( p=0.011), urea (p=0.014), SGOT (p=0.007), SGPT (p=0.030) and alkaline phosphatase (p=0.002) in icteric serum added and not added potassium ferric cyanide.